Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1007/s00280-005-1006-3
|View full text |Cite
|
Sign up to set email alerts
|

Irinotecan combined with docetaxel in pre-treated metastatic breast cancer patients: a phase II study

Abstract: The irinotecan-docetaxel combination produces quite a high response rate in pre-treated advanced breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…An additional 8 patients showed stable disease. In the study from Greece (Stathopoulos et al, 2005), 48 patients pre-treated with anthracycline-combined chemotherapy, 30 patients were also treated with paclitaxel and 2 with docetaxel, were enrolled. All patients had WHO performance status of 0-2.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An additional 8 patients showed stable disease. In the study from Greece (Stathopoulos et al, 2005), 48 patients pre-treated with anthracycline-combined chemotherapy, 30 patients were also treated with paclitaxel and 2 with docetaxel, were enrolled. All patients had WHO performance status of 0-2.…”
Section: Discussionmentioning
confidence: 99%
“…Via steps of screening the title and reading the abstract, 5 studies were identified (Frasci et al, 2005;Stathopoulos et al, 2005;Moulder et al, 2008;Lee et al, 2013;Otsuka, et al, 2013). These studies had been carried out in China, Japan, Korea, Europe and the USA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, several studies are evaluating the efficacy of CPT-11 in the treatment of solid tumors (Conroy et al, 2005;Delord et al, 2005;Reardon et al, 2005;Stathopoulos et al, 2005). Metabolism of CPT-11 is complex with the involvement of several enzymatic reactions (Rivory, 2000;Slatter et al, 2000).…”
mentioning
confidence: 99%